Reconstructing Regional Trajectories: the Provenance and Distribution of Archaic to Hellenistic Ceramics in Central Pisidia (South‐west Turkey). (11th August 2016) - Braekmans, D.; Degryse, P.; Neyt, B.; Waelkens, M.; Poblome, J.
Abstract : Analytical ceramic studies offer the opportunity to determine cultural development and change on the basis of origin and use of raw materials. In this particular study, an archaeometric approach on ceramics in central Pisidia contributes to the discussion of contact and exchange between indigenous communities and several cultural spheres of influence on a long‐term timescale (eighth to second centuriesbce ). Morphological data as well as mineralogical (optical microscopy; n = 273) and chemical composition (by ICP–OES/MS; n = 122) of ceramics and raw materials show distinct resource zones for the production and distribution of ceramics in this connecting region of Anatolia. The use of trace element profiles (REE, HFSE, LILE and TTE) in particular is regarded as instrumental in detailing high‐resolution provenancing of ceramics. The ceramic provenance indicates different patterns of material interactions during the Archaic, Classical and Hellenistic periods. A significant increase in regional interaction occurs coinciding with the development of pottery activities at Sagalassos.